Morphology and Morphometry of Rhinencephalon of Brain of Surti Buffalo (Bubalus bubalis) - Suman, Alka; Pandya, Sweta; Shukla, Vanila (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The morphological and morphometrical study of brain of Surti buffaloes was conducted on all the structures of the rhinencephalon which were located on the ventral surface of the cerebral hemispheres. The structures included paired olfactory bulb,olfactory tract,lateral and medial olfactory striae and pyriform lobe. The olfactory bulbs were oval, hollow structures which continued caudally with the olfactory tract. The overall mean length and width of right bulb were 3.45±0.06 and 1.46±0.03 cm, while those of left bulb were 3.42±0.06 and 1.43±0.03 cm, respectively. The olfactory tracts were short,wide and flat bands which divided caudally into two lateral and medial striae. The pyriform lobes were two pear shaped structures.
Keywords: Buffalo; Rhinencephalon; Morphometry; Olfactory bulb; Pyriform lobe